Implication of al-Attas’s Islamic philosophy of science on science education - Martanegara, Irfan Habibie (Ibn Khaldun Journal of Social Science, 2019)
Science education is often suspected as a cause, not only student become far from God, furthermore make students have secular thinking. Therefore, this paper aims to reconstruct the concept of science education based on the ideas of Syed Muhammad Naquib al-Attas on the Islamic philosophy of science. With the Islamic concept of science education, students are expected to increase piety to God. This paper discusses the thought of al-Attas on the Islamic philosophy of science in his works such as “Islam and the Philosophy of Science”, “The Positive Aspects of Tasawwuf: Preliminary Thoughts on an Islamic Philosophy of Science”, and “The Concept of Education in Islam”. After that, this paper attempts to extract the Islamic philosophy of science, especially ontology and epistemology, into science education concept. This paper concludes that there are several implications of the Islamic philosophy of science in science education. First, the purpose of Islamic Science education is to understand science as God’s way of governing the universe. Second, science education should integrate the revelation with reason and the senses as a source of scientific knowledge. Third, science education should also teach students environmental awareness. Fourth, science education should pay attention to the language in the teaching of science. And lastly, science education should taught a prayer and worship perfection as one way to gain scientific knowledge.